Inhibitory effects of climate change on the growth and extracellular enzyme activities of a widespread Antarctic soil fungus - Misiak, Marta; Goodall‐Copestake, William P.; Sparks, Tim H.; Worland, M. Roger; Boddy, Lynne; Magan, Naresh; Convey, Peter; Hopkins, David W.; Newsham, Kevin K. (Wiley, 2020)
Temperatures approaching or exceeding 20 °C have been measured during summer in polar regions at the surfaces of barren fellfield soils under cloudless skies around solar noon. However, despite the upper temperature limit for the growth of cold‐adapted microbes – which are abundant in polar soils and have pivotal roles in nutrient cycling – typically being close to this temperature, previous studies have not addressed the consequences of climate change for the metabolism of these organisms in the natural environment. Here, in a five‐year field experiment on Alexander Island in the southern maritime Antarctic, we show that the abundance of Pseudogymnoascus roseus, the most widespread decomposer fungus in maritime Antarctic fellfield soils, is reduced by 1–2 orders of magnitude when irrigated and nutrient‐amended soils are warmed to >20 °C during summer. Laboratory experiments under conditions mimicking those during midsummer in the natural environment indicated that the hyphal extension rates of P. roseus isolates and the activities of five extracellular enzymes are reduced by 54–96% at high water availability after exposure to temperatures cycling daily from 2–21 °C and 2–24 °C, relative to temperatures cycling from 2–18 °C. Given that the temperatures of surface soils at the study site already reach 19 °C during midsummer, the observations reported here suggest that, at predicted rates of warming arising from moderate greenhouse gas emissions, inhibitory effects of climate change on the metabolism of P. roseus could manifest themselves within the next few decades. Furthermore, with peak temperatures at the surfaces of fellfield soils at other maritime Antarctic locations and in High Arctic and alpine regions already exceeding 20 °C during summer, the observations suggest that climate warming has the potential to inhibit the growth of other cold‐adapted microbes, with negative effects on soils as the Earth’s climate continues to warm
Keywords: extracellular enzymes; Antarctica; climate warming; cold adaptation; growth inhibition; psychrotrophy; soil fungi water